The Ukraine war in Western political cartoons during the first year and a half of the conflict - Morales Domínguez, Lucas; Zurita Andión, José Luis; Arrufat Martín, Sandro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This article uses the methodology of multimodal discourse analysis, applied to a sample of 277 political cartoons from around the world, categorizing the most commonly used resources in constructing the Western message. For this purpose, 33 cognitive subframes have been established, covering a period extending beyond the first year of the conflict, from the days preceding the invasion to the assassination of Yevgueni Prigozhin, leader of the Wagner Group.